Study of Odonata Diversity in Kerangas Forest Sukadamai Village and Punai Beach Simpang Pesak, Belitung Timur - Purwanto, Pratama Bimo; Zaman, Mokhammad Nur; P, Abellia Ike; Akbar, Mushawir; Arief, Marwan (Proceeding International Conference on Science and Engineering, 2019)
Belitung is known as the biggest tin mining in Indonesia. Besides that, Belitung also has a lot of biological resources, that is Odonata (dragonfly). The research was conducted in June 2018 by exploration in Belitung, particularly in Punai beach and Kerangas forest (ex-tin mining) area. There is found 17 type of dragonfly such as Ichtinogomphus decoratus., Macrogomphus sp., Orthetrum sabina., Nannophya pygmaea., Neurothemis fluctuans., Rhodothemis rufa., Rhyothemis phyllis., Urothnemis signata., Pseudagrion coomansi., Ceriagrion cerinorubellum., Acisoma panorpoides., Brachydiplax chalybea., Diplacodes nebulosa., Orthetrum pruinosum., Agriocnemis femina., Agriocnemis pygmaea., and Ischnura senegalensis. All species were conducted to find out the diversity using Shannon-Wiener index and resulting 2,77 index.